Oral health status among children receiving chemotherapy - Fayhaa A Al-Mashhadane (University of Mosul, College of Dentistry, 2007)
Aim: To investigate the effects of chemotherapeutic agents on the oral health of children and to com-pare the action of two mouth rinses chlorhexidine digluconate 0.2 % and salty water (0.9% NaCl) in relation to their ability in controlling the plaque and gingival inflammation with children treated by cytotoxic agents. Materials and Method: In this clinical trial, the selected children were divided into two groups the first one comprised of 30 healthy children represented as a control group and the second one comprised of 30 children who were receiving chemotherapy for at least 6 months, they were se-lected from patients attended to pediatric wards of public hospitals in Mosul city .All children were of similar age groups and mean age of 5+ 1 years. The plaque and gingival indices were measured accord-ing to silness and lِöe for the six teeth at the baseline. Then the 30 children who were receiving chemo-therapy were randomly divided into two groups; each consisting of 15 children, they were instructed to use mouth rinses twice daily for 30 seconds after breakfast and before the bed time.The plaque and gingival indices were again measured one month after mouth rinsing for the six teeth at the baseline. Results: The results of this study revealed that the chemotherapeutic agents modify oral health and there was significant increase of plaque and gingival indices in children receiving chemotherapeutic agents (at p≤0.05), also results showed that there was a significant reduction after rinsing with chlor-hexidine digluconate for plaque and gingival indices (at p≤0.05), while non significant change for salty water mouth wash. Conclusion: In view of the possible factors that causes increase of the plaque and gingival indices, suggested myelosuppresion that is associated with chemotherapy which has effects on rate and pattern of hard and soft tissues resulting in reduced the ability to repair and maintain the oral health status.